Inicios y finales de los tratados del Corpus Hippocraticum - Rodríguez Alfageme, Ignacio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2007)
The study of the phrases that open and close the writings of the Corpus Hippocraticum allows to establish several prototypal beginnings that relate to its oral or written character.